PENDUGAAN POTENSI KEKERINGAN METEOROLOGIS TERHADAP KEBAKARAN HUTAN DAN LAHAN DENGAN METODE INDEKS PRESIPITASI TERSTANDARISASI DI KABUPATEN BANJAR - Dedy Supratono; Fakhrur Razie; Mahrus Aryadi; Badaruddin Badaruddin (Universitas Lambung Mangkurat, 2016)
The potency of meteorological drought estimated by Standardized Precipitation Index can be used to predict the incidence of forest and land fires in Kabupaten Banjar. The aim of this research was to synthesize the relationship rainfall and level of dryness with the occurrence of hotspots, mapping meteorological drought in monthly periods and level of dryness of the method of Standardized Precipitation Index (SPI) and spreading of hotspots in Kabupaten Banjar. This research was conducted in Kabupaten Banjar by using the method of Standardized Precipitation Index to analyze the dryness level in one area. Data used were the processed monthly rainfalls in the period of 2010 – 2015 and the data of hotspots in Kabupaten Banjar, and then the maps for the hotspots and rainfall were created using mapping software. The results showed meteorological drought periods in Kabupaten Banjar happens nearly every year with the lowest period (very dry) occurred in November 2015 with a value of SPI -3.3. To conclude, first, the less rainfall and the low value of SPI will be followed by the increasing incidence of forest and land fires on the marks with the high number of hotspots, the second level of meteorological dryness occurs in January, July and up to November, and the last occurrence of high hotspots occurs in July up to November.